Rare case of congenital tracheal diverticulum presenting as tubercular diverticulitis: a case report - Chakrabarty, Chayan; Chaudhry, Anil; Arora, Tannistha (International Journal of Advances in Medicine, 2025)
Congenital tracheal diverticulum (DV) is often discovered incidentally during imaging unless the patient becomes symptomatic. We report the case of a young female who presented with a 10-week history of cough accompanied by minimal sputum production and weight loss. Due to a mismatch between chest X-ray findings and sputum results, a high-resolution CT scan of the chest was performed, which revealed normal lung parenchyma but demonstrated a multiloculated tracheal DV. Bronchoscopic evaluation identified a small opening of the DV in the central portion of the trachea. Microbiological analysis of the bronchial wash tested positive for Mycobacterium tuberculosis (MTB) on both CBNAAT and MGIT. The patient made a complete clinical and radiological recovery in response to standard antitubercular treatment. Based on clinical presentation, imaging, and microbiological evidence, a diagnosis of congenital tracheal DV with tubercular diverticulitis was made-an extremely rare presentation that, to the best of our knowledge, has not been previously reported.